2004
DOI: 10.1007/s10201-004-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Trophic coupling of a testate amoeba and Microcystis species in a hypertrophic pond

Abstract: Seasonal changes in abundance of the testate amoeba Penardochlamys sp. and its food vacuole contents were investigated in relation to blooms of the cyanobacteria Microcystis spp. in a hypertrophic pond from April 1999 to March 2000. The behavior of the amoeba feeding on M. aeruginosa and M. wesenbergii was also observed in the laboratory. The amoeba was detectable from late May to November 1999 during the blooms of Microcystis spp. Cell densities of the amoeba fluctuated between 1.4 and 350 cells ml Ϫ1 with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
2
21
1
1
Order By: Relevance
“…Lansac-Tôha et al 2009). However, our results indicate that this group is a poor indicator of eutrophication (but see Branco et al 2002;Nishibe et al 2004). The inclusion of this group in biomonitoring programs is, probably, only justified to evaluate the impacts derived from hydrological changes caused by river damming (Lansac-Tôha et al 2009).…”
Section: Discussionmentioning
confidence: 79%
“…Lansac-Tôha et al 2009). However, our results indicate that this group is a poor indicator of eutrophication (but see Branco et al 2002;Nishibe et al 2004). The inclusion of this group in biomonitoring programs is, probably, only justified to evaluate the impacts derived from hydrological changes caused by river damming (Lansac-Tôha et al 2009).…”
Section: Discussionmentioning
confidence: 79%
“…Previous laboratory studies have demonstrated that some species of flagellates, including the heterotrophic flagellate Collodictyon triciliatum and the mixotrophic flagellate Poterioochromonas sp. (Nishibe et al 2002, Ou et al 2005, and rhizopods (Nishibe et al 2004) graze on Microcystis populations. While amoeboid grazing is relatively well understood there is less information regarding flagellate grazing on Microcystis populations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported as possible grazers of Microcystis: protists (Cole and Wynne 1974;Dryden and Wright 1987), rotifers (Snell 1980;Fulton and Paerl 1987), crustacean zooplankton (Hanazato and Yasuno 1984;Jarvis et al 1987), and fish (Moriarty 1973;Kawanabe and Mizuno 1989;Miura 1990). There are only a limited number of rotifers, crustaceans, and fish that graze on Microcystis, but various protistan species have been shown to do so (Zhang et al 1996;Nishibe et al 2002Nishibe et al , 2004Kim et al 2006;Wilken et al 2010). Thus, it is possible that the wax and wane of a Microcystis bloom are dependent on grazing by protists.…”
Section: Introductionmentioning
confidence: 92%
“…Among such protistan grazers, rhizopods, including both naked and testate amoebae, are frequently found to be abundant when significant decreases in Microcystis abundance are detected in lakes, and grazing on Microcystis by some rhizopod species has been demonstrated in laboratory experiments (Yamamoto 1981;Yamamoto and Suzuki 1984;Nishibe et al 2004) and field observations (Whitton 1973;Nishibe et al 2004). Unfortunately, we still have limited eco-physiological information about the rhizopods that graze on Microcystis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation